1995
DOI: 10.1093/nar/23.19.3822
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation ofcdc25Ctranscription is mediated by the periodic repression of the glutamine-rich activators NF-Y and Sp1

Abstract: The late S/G2-specific transcription of the human cdc25C gene is dependent on an initiator-proximal repressor element (CDE) and an upstream activating sequence (UAS) of undefined nature. We now show that these upstream sequences harbour multiple in vivo protein binding sites that interact with transcriptional activators and form separable, context-independent functional modules. Major components of the UAS are a bona fide Sp1 site and three direct sequence repeats (Yc-boxes). The Yc-boxes interact with the CCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 35 publications
5
90
1
Order By: Relevance
“…The hypothesis that these fluctuations in mRNA levels are based, at least in part, on promoter function is supported by results from both transient transfections with various promoter/luciferase constructs and by experiments using the stably transfected cell lines. Finally, both the presence in the PLK promoter of CDE and CHR sequences similar to those found in cdc2, cyclin A, and cdc25C promoters (12,22,23), and the fact that mutations of the CDE and CHR sequences of PLK caused elevated G 1 luciferase activity, also support a role for promoter function in the control of mRNA levels.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The hypothesis that these fluctuations in mRNA levels are based, at least in part, on promoter function is supported by results from both transient transfections with various promoter/luciferase constructs and by experiments using the stably transfected cell lines. Finally, both the presence in the PLK promoter of CDE and CHR sequences similar to those found in cdc2, cyclin A, and cdc25C promoters (12,22,23), and the fact that mutations of the CDE and CHR sequences of PLK caused elevated G 1 luciferase activity, also support a role for promoter function in the control of mRNA levels.…”
Section: Discussionmentioning
confidence: 59%
“…Potential binding sites for SP1 were previously identified in the promoters of cyclin A, cdc2, and cdc25C genes (12,22). However, we did not detect cell cycle regulated binding to the GC-rich SP1 containing PLK oligonucleotide in electrophoretic mobility shift assays, nor did mutation of the SP1 site block cell cycle regulation of the promoter/luciferase construct (data not shown).…”
Section: Fig 9 Sequence Homologies Of the Cde/chr Element Of Plkmentioning
confidence: 52%
See 2 more Smart Citations
“…The trypsinized cells were stained with Hoechst 33258 and sorted according to DNA content using a Becton-Dickinson FACStar Plus (Lucibello et al, 1995) Figure 2 Genomic DMS footprinting of the cdc25C promoter in sorted G 1 and G 2 fractions of WI38VA13 cells. The positions of the CDE and the NF-Y binding sites (Lucibello et al, 1995;Zwicker et al, 1995a) are indicated. In vivo footprinting was performed exactly as described (Lucibello et al, 1995;Zwicker et al, 1995b).…”
mentioning
confidence: 99%